TATA SPASIAL PERMUKIMAN TRADISIONAL MANGGARAI BERDASAR RITUAL PENTI DI KAMPUNG WAE REBO DI PULAU FLORES - Perdana, Mohammad Raditya (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 2 (2016): Agustus 2016, 2016)
In the Lesser Sunda Islands of the Indonesian Republic a Kampung is located in Flores Island. It is called Kampung Wae Rebo and constitutes the focus of this paper. Here the formation of traditional settlements with their ritual practices has a dominant role. Here, culture is the determining factor that shapes the living environment. The Manggarai ethnic group who live in Wae Rebo is well known for their enduring perpetuation of tradition. One such tradition is selected for in-depth study - that of the annual ceremony of penti . This takes the form of a giant ritual pertaining to the agricultural life of the community . Here a series of activities relating to this ritual have affected the spatial formation of the Wae Rebo settlement in unique ways. The study methodology deploys concepts derived from both structuralism and hermeneutics. In conclusion the following paper suggests that the existence of Wae Rebo settlement has been historically determined by five elements, namely; the social structure of the community; ritual practices; harmony with nature; defence from both internal and external forces; and the adaptive qualities of culture. Keywords: spatial arrangement; traditional settlement; Kampung Wae Rebo ; ritual penti Abstrak Di Kepulauan Sunda Kecil, tepatnya di Pulau Flores, terdapat Kampung Wae Rebo dengan pola permukiman tradisional yang didominasi oleh praktek-praktek ritualnya. Dalam konteks ini, budaya merupakan faktor determinan dalam proses pembentukan permukimannya. Suku Manggarai merupakan sekelompok etnik di Kampung Wae Rebo yang mempertahankan tradisi ini secara turun-temurun. Salah satu tradisi yang menjadi fokus penelitian ini adalah ritual tahunan penti . Ritual ini merupakan praktek budaya bertani yang dilakukan oleh masyarakatnya. Rangkaian ritual ini telah mempengaruhi keunikan pola permukiman kampung ini. Studi ini dilakukan melalui pendekatan structuralism dan hermeneutics. Pada akhirnya, eksistensi permukiman Kampung Wae Rebo secara kebersejarahannya ditentukan oleh lima element, diantaranya: struktur masyarakatnya; praktek-praktek ritual; keharmonisan dengan alam; pertahanan dari faktor eksternal dan internal; dan adaptasi budaya.
Keywords: tata ruang; permukiman adat; Kampung Wae Rebo; ritual penti